Extensive mapping of an innate immune network with CRISPR. Issue 7 (24th July 2015) - Aregger, Michael; Hart, Traver; Moffat, Jason
<x xml:space="preserve">Abstract</x> The application of the CRISPR‐Cas9 system marks a major breakthrough for genetic screens, particularly in mammalian cells where high‐throughput targeted gene editing has been lacking. Parnas et al (2015) apply this screening technology to mouse bone marrow‐derived dendritic cells in order to study the regulation of the immune response triggered by PAMPs. Through integrated analysis of gene knockouts in conjunction with changes in protein and mRNA expression, CRISPR screens are facilitating dissection of immune regulatory networks at unprecedented resolution.